Life Satisfaction and Psychological and Physical Well-Being - Kumar, V. K.; Tahmaseb-McConatha, Jasmin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint showcases a review and empirical studies on life satisfaction and its related aspects. The studies are from several countries on a wide range of samples including university students, faculty, nurses, entrepreneurs, adolescents, national databases, refugees, and community samples.